The Problems of Formation of Communicative Competence of Higher Educational Institutions Students (Eurasian Journal of Learning and Academic Teaching, 2022)
The article under discussion reveals the formation of communicative competence of students in non-linguistic higher educational institutions. The role and aspects of learning English in a technical university based on the concept of competence approach and in the context of multi-disciplinary education had been analyzed. The author considers some methodological principles and peculiarities of teaching a foreign language in a technical university, based on the criteria of professional competence development.